Reproduction and Sexuality in Marine Fishes : Patterns and Processes - Cole, Kathleen S. (Kathleen Sabina), 1950- (Book collections on Project MUSE., 2010)
Marine fishes represent astonishing diversity with respect to practically every aspect of their biology. Reproductive modes and sexual patterns are especially fascinating and provide deep insight into general evolutionary problems. In this volume, chapters focus on reproduction and sexuality among groups of fishes defined by habitat, taxon, and the reproductive processes that are critical for reproductive success. The book illustrates how knowledge of reproductive biology among marine fishes can help identify vulnerable and potentially vulnerable species in the face of changing environmental conditions and increasing human-based pressures.